Urgensi Penanganan Tindak Pidana Perdagangan Manusia di Kamboja Menurut Tinjauan Hukum Internasional - Nealam Callista; Adinda Sawitri; Risma Alya Roshanti; Putri Rahmawati; Loso Loso; Ganis Vitayanty Noor (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Human trafficking is a serious and growing crime, including in Cambodia, which has become one of the countries vulnerable to this practice. This study aims to analyze the handling of human trafficking crimes in Cambodia from an international law perspective. Cambodia plays a significant role in the context of human trafficking due to its geographic location and socio-economic conditions, which influence the rate of human trafficking, whether for sexual exploitation, forced labor, or organ trafficking. This research uses a qualitative method with a literature review approach from various sources, including international conventions, reports from international organizations, and Cambodia's national regulations. The findings show that although Cambodia has adopted several laws to combat human trafficking, the implementation of these policies is often hindered by limited resources, corruption, and lack of cooperation between countries. Additionally, despite efforts from the international community, such as the Palermo Protocol, challenges in consistently applying the law remain a significant barrier. The study also finds that stricter law enforcement and better rehabilitation systems for victims are necessary to improve the situation. Therefore, further collaboration between the Cambodian government, international organizations, and non-governmental organizations is needed to comprehensively address this issue.